Los desafíos de la educación inicial en la actualidad - Elena Valdiviezo Gaínza (Pontificia Universidad Católica del Perú, 2011)
The challenges of early childhood education nowadays This article shows, in summary form, some socioeconomic characteristics of modern society, including globalization, multiculturalism, inequality and social and economic gaps, changes in science and technology and its relation to early childhood education It also explains the various paradigms and conceptions of development and vision of childhood and education, leading to a profound renewal of the educational prospects. Keywords: globalization, multiculturalism, early childhood, paradigms, holistic approach, systemic approach, complex thinking, inclusive education, education for diversity